Exploring Academic Leadership of University Teachers under the Chinese Contemporary Philosophy and Social Science (Xin Wen Ke) Construction Innovation Context. Issue 5 (2nd November 2021) - Liusheng, Liu; Wenlong, Song; Meng, Shi; Shijun, Cha
Abstract: Chinese Xin Wen Ke construction innovation is the integration of philosophy and social science, scientific technology, and industry, with the combination of diverse academic subjects and concentrations. Through academic orientation, resources integration, and behavioral modeling, academic leadership of university teachers can be effectively promoted, and the applicative solutions for the emerging obstacles in the process of the combination can be provided. It also can boost the quality of academic leadership of university teachers in relation to orientating values and philosophies, locating the goals, promoting cooperation, and refining achievements. According to recent research, to analyze the contents and structures can foster the quality development in academic leadership of university teachers. This article will draw an overall assessment on different components of academic leadership of university teachers under Chinese Xin Wen Ke construction innovation context, including research reviews and definitions, functions, structures analysis, and cultivation methods, aiming to provide evidence to demonstrate its significance.